Sport reserve training system in municipal districts - Abramov, E. N.; Obukhov, S. M.; Rodionov, V. A.; Peshkov, A. A.; Murtazin, S. N. (Theory and Practice of Physical Culture, 2017)
Success of the sport reserve training system reform in the Russian Federation on the whole will largely depend on how efficient the local reform processes are at the regional and municipal levels. Objective of the study was to analyze the frame versions of the sport reserve training system reform for the poorly populated rural municipal districts. At this juncture, four frame versions of the sport reserve training system reform for the poorly populated rural municipal districts may be offered to cater for the needs of these legally and communally specific entities. We believe that the sport reserve training system reform is to be designed to protect the integrity of the existing Children and Youth Sport Schools (CYSS) network under control of the relevant different agencies and take due actions to further their integration within the national physical culture and sports sector. The reform will be geared to step up the role of the municipal-level CYSS in the sport reserve training system reform and at the same time retain and advance the efficiency of the mass sport movements and missions.